Accelerating the transformation to a sustainable food economy by strengthening the sustainable entrepreneurial ecosystem - Forrest, Nigel; Wiek, Arnim; Keeler, Lauren Withycombe (Frontiers in Sustainable Food Systems, 2023)
Strengthening the sustainable entrepreneurial ecosystem (SEE), particularly its support functions for small to medium-sized enterprises (SMEs), is increasingly seen as an important means of accele-rating the transformation to a sustainable economy. Little is known, however, about how to strengthen SEEs. In this article, we evaluate a series of 16 projects intended to develop SEE functioning to accelerate transformation to a sustainable food economy in the Greater Phoenix Area of Arizona. We use an evaluative framework designed around a set of ten SEE support functions to qualitatively assess the baseline state of the SEE, how projects were executed, the effects of these projects, and the overall changes in the SEE that resulted. The findings indicate all but one projects had positive effects on the SEE (nine weak, six medium). In conjunction with other developments, the projects raised the overall SEE performance from the baseline state of two functions being performed at only minimal level, to seven functions being performed, including one at a medium level. Insights gained from comparing results across projects suggest tentative guidelines for future practice, which should be useful for SEE stakeholders, including policy makers, economic development agencies, financial institutions, consultants, and educa¬tors, interested in strengthening SEEs. Researchers engaging in studies on strengthening SEEs may benefit from the evaluative frame¬work enabling larger cross-case comparisons.